Philosophy of Education and Its Significance - Supriyanto, Supriyanto (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2019)
Education is a very important capital of life in the lives of humanity. However, education sometimes cannot develop sustainably without being approached with a philosophical approach. Education requires philosophy to open its perspective in order to be able to respond to various actual problems that always arise in the world of education. The nature of education is a process of learning and searching, as well as the development of knowledge that has no finishing point. In this frame of meaning, true education is an intellectual, emotional, as well as spiritual ascent all towards new peaks. And one of the keys that is able to uncover that awareness is philosophy. Therefore, this paper will try to explore the understanding and meaning of educational philosophy, the significance of philosophy on education, educational goals, and concludes with a conclusion.